Evaluación de desempeño del personal que labora en la empresa “Ricuras de Sal y Dulce” y su incidencia en el rendimiento laboral. - Sarmiento Sarmiento, Gissella Nicole (2023)
In today's business world, personnel performance evaluation has become an essential tool for organizations seeking to optimize their operation and achieve their objectives. The present research aims principaly to evaluate the work performance of the personnel working in the company Ricuras de Sal y Dulce in Loja city. It is a descriptive research, with a mixed approach, 11 employees participated, consisting of 6 cooks, 3 waiters and 2 cashiers. The performance evaluation method used was the 360o method because it is the most complete and involves: boss, colleagues, customers and their self-evaluation; the technique used was the survey through a questionnaire where 8 competencies were evaluated: Communication, Teamwork, Conflict Resolution, Continuous Improvement, Organization and Time Administration, Customer Focus, Critical Thinking and Training, taking into account the use of a Likert scale to rate from 1 to 5, being (1,2) negative and (3,4,5) positive. The results indicated that the competency with the highest incidence is critical thinking (93.86%), while the competencies with the lowest incidence are conflict resolution (83.33%) and communication (85.76%), leading to the fact that communication problems cause conflict resolution in the labor area. In individual performance, the worker with the lowest performance is a cashier, showing that the most difficult competencies to cope with are problem solving (65%) and continuous improvement (70%). On the other hand, the worker with the highest performance is another cashier evidencing critical thinking (100%) and customer focus (97%); it was comunicated the results of their work performance to each of the workers. Finally, the competencies presented in the majority of partners have an impact (93.86%) on their performance.